Calcium oxalate crystals in floral organs of Helianthus annuus L. and H. tuberosus L. (Asteraceae) - Meric, Ciler; Dane, Feruzan (Acta Biologica Szegediensis, 2004)
Helianthus annuus L. and Helianthus tuberosus L. belong to Asteraceae that is one of the greatest families of plant kingdom. Calcium oxalate crystals are found in most organs and tissues of many plant species. The type, morphology and distribution of calcium oxalate crystals in floral organs of H. annuus and H. tuberosus were studied. Crystals were investigated at light and electron microscopy levels. CaOx crystals in calyx and bracts both of H. annuus and H. tuberosus were not observed. The ligulate and tubulate corollas of H. annuus had styloid and prismatic crystals. Also in both of the ligulate and tubulate corollas of H. tuberosus were observed prismatic and styloid crystals as similar with H. annuus. Styloid and prismatic types of CaOx crystals in filaments of H. annuus and H. tuberosus were determined. In endothecial layer and tapetum cells of anthers of both of taxa only styloid type crystals were observed. The ovary was not contains CaOx crystals in H. annuus and H. tuberosus, Style of both of taxa had styloid shape crystals. But in stigma trichomes of H. annuus and H. tuberosus druses were found. The raphides were not observed in both of taxa. This study provides additional knowledge about the presence of CaOx crystals in Asteraceae.